PENGARUH JAHE (ZINGIBER OFFICINALE) HANGAT DALAM MENGURANGI EMESIS GRAVIDARUM DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA PEKANBARU - Harida wati (STIKes Al-Insyirah Pekanbaru, 2020)
Gravidarum emesis occurs due to the increasing levels of the hormones Estrogen, Progesterone and Human Chorionic Gonadotropine (HCG) in the serum of the placenta. Ginger is a way to relieve nausea and vomiting during pregnancy. The purpose of this study was to analyze the effect of giving warm ginger steeping in reducing emesis gravidarum in the Work Area of ​​the Puskesmas Harapan Raya Pekanbaru. This type of research is quantitative with one group pretest-posttest design. This research was conducted in the working area of Puskesmas Harapan Raya in April 2019. The population of this study was first trimester pregnant women who experienced nausea and vomiting with a sample of 14 respondents, the sampling technique was purposive sampling. The measuring instrument in this study is the observation sheet. Data analysis used univariate and bivariate analysis. Univariate results were obtained before administration of ginger steeping, the majority of respondents experienced emesis, moderate by 85.7% and after giving ginger steeping, the emesis condition of the respondents decreased to mild emesis by 78.6%. Paired Sample T-test test results obtained p value = 0,000 (p-value <α = 0.05). Based on these results it can be concluded that steeping warm ginger is very influential in reducing emesis gravidarum in the Work Area of the Puskesmas Harapan Raya Pekanbaru. Suggestion, It is expected that pregnant women consume ginger steeping which has been proven effective in reducing nausea and vomiting.